Generative AI: creating innovative marketing and sales content - Mendoza, Jose (Henry Stewart Talks, 2026)
Generative AI in sales strategies, Maximizing the effectiveness of generative AI, Overcoming obstacles in integration, Generative AI tools, Integrating generative AI into your marketing and sales strategy, Ethical concerns and challenges with generative AI